Organización de la Contabilidad de Costos por Órdenes de Producción en la Empresa “Arte Mueble” de la Ciudad de Yantzaza. Periodo 01 de Abril al 30 de Junio 2022. - Cabrera Quizhpe, Angélica Mishell (2023)
The curriculum integration work called ORGANIZATION OF COST ACCOUNTING BY PRODUCTION ORDERS IN THE COMPANY “ART MOBILE” OF YANTZAZA CITY. PERIOD APRIL 1ST TO JUNE 30TH 2022. It was carried out in compliance with what determines the Regulation of Academic Regime of the National University of Loja, in order to apply a system of costs that meets the needs of the business, that allows the owner of the owner of the economic activity with craft qualification to determine the total and unit costs incurred in the production of the different types of furniture and its parts, thus determining the profitability of the economic activity. In order to comply with the objectives set out in this Curriculum Integration Work, first the inventory of materials in physical form was made, verify ing the presence of existing products for sale, with this, a plan and manual of accounts was developed, coupled to the company, which were used in the development of the accounting process; by reviewing the documentation, the accounting process was executed, building accounting and auxiliary records according to the needs of the Company “Arte & Mueble”. Followed, the formats involved in this process for obtaining the costs were designed, for the treatment of the raw material production orders, requisition o f materials, Kardex cards were used; sim ilarly for labor clock cards, time cards, work panel, role of payments and provisions, and other cost records, which was done by reviewing source documentation, files and thesis, same that helped to get the unit and total production cost of each production order. To other, the accounting process was developed by the System of Costs by Production Orders, with the information provided began to make the Initial Situation Status, Consequently, the journal entries of the transactions in the daily book with their respective distribution for the preparation of the Trial Balance and the worksheet and the corresponding adjustments, allowing the presentation of the financial statements.